Does bacterial vaginosis modify the effect of hormonal contraception on HIV seroconversion: a prospective cohort study - SABO, Michelle C. (AIDS, 2019)
OBJECTIVES: A recent study of HIV serodiscordant couples found that depot medroxyprogesterone acetate (DMPA) and oral contraceptive pills (OCPs) were associated with increased HIV risk in the presence, but not in the absence, of bacterial vaginosis (BV). We assessed whether BV is an effect modifier of the association between hormonal contraception and HIV seroconversion in female sex workers (FSWs) in Mombasa, Kenya. DESIGN: Prospective cohort study. METHODS: Data collected from HIV-negative FSWs from 1993–2017 were analyzed. Cox proportional hazards models were used to assess the relationship between HIV seroconversion and use of DMPA, OCPs, or hormonal contraceptive implants (Norplant, Jadelle). RESULTS: A total of 1,985 women contributed 7,127 person-years of follow-up; 307 women seroconverted to HIV (4.32/100 person-years). DMPA was significantly associated with elevated risk of HIV seroconversion in women with (aHR 1.56, 95% confidence interval [CI] 1.08–2.25; p=0.02) and without (aHR 2.08, 95%CI 1.46–2.97; p<0.001) BV (interaction p=0.4). Similarly, OCP use was associated with increased HIV risk both in the presence (aHR 1.50, 95%CI 0.94–2.39; p=0.09) and absence (aHR 1.61, 95% CI 0.99–2.64; p=0.06) of BV (interaction p=0.9), though neither stratum reached statistical significance. Implants were not associated with HIV seroconversion overall, (aHR 0.99, 95%CI 0.40–2.45; p=0.9), or in women with (aHR 0.65, 95% CI 0.16–2.72; p=0.6) and without (aHR 1.39, 95% CI 0.43–4.46; p=0.6) BV (interaction p=0.5). CONCLUSIONS: Bacterial vaginosis had no effect on the associations between hormonal contraceptives and HIV seroconversion in this cohort. Contraceptive implants were not associated with increased HIV risk compared to no contraception.